A class of BVPs for nonlinear fractional differential equations with p-Laplacian operator - Zhenhai Liu; Liang Lu (Electronic Journal of Qualitative Theory of Differential Equations, 2012)
In this paper, we study a class of integral boundary value problems of nonlinear differential equations of fractional order with p-Laplacian operator. Under some suitable assumptions, a new result on the existence of solutions is obtained by using a standard fixed point theorem. An example is included to show the applicability of our result.